2019
DOI: 10.1681/asn.2018090886
|View full text |Cite
|
Sign up to set email alerts
|

An Organizational-Level Program of Intervention for AKI: A Pragmatic Stepped Wedge Cluster Randomized Trial

Abstract: Background Variable standards of care may contribute to poor outcomes associated with AKI. We evaluated whether a multifaceted intervention (AKI e-alerts, an AKI care bundle, and an education program) would improve delivery of care and patient outcomes at an organizational level. Methods A multicenter, pragmatic, stepped-wedge cluster randomized trial was performed in five UK hospitals, involving patients with AKI aged $18 years. The intervention was introduced sequentially across fixed three-month periods acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
131
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 35 publications
5
131
0
3
Order By: Relevance
“…One of the greatest challenges for embedded pragmatic trials is achieving adherence to the intervention. Lower than desired uptake of the care bundle components likely reduced the effect of the intervention in the trial by Selby et al 2 This trial may be the first in nephrology to use stepped wedge cluster randomization. Cluster randomization is often used in pragmatic trials to simplify implementation of the intervention by clinical personnel and reduce the likelihood of contamination across treatment arms.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…One of the greatest challenges for embedded pragmatic trials is achieving adherence to the intervention. Lower than desired uptake of the care bundle components likely reduced the effect of the intervention in the trial by Selby et al 2 This trial may be the first in nephrology to use stepped wedge cluster randomization. Cluster randomization is often used in pragmatic trials to simplify implementation of the intervention by clinical personnel and reduce the likelihood of contamination across treatment arms.…”
mentioning
confidence: 93%
“…Specific strategies for supportive care have been recommended in consensus guidelines, but they have not been tested in rigorous randomized clinical trials. 1 In this issue of the Journal of the American Society of Nephrology, Selby et al 2 report the results of a multicenter, pragmatic, stepped wedge cluster randomized trial of a multicomponent supportive care intervention for AKI. The trial was conducted in five hospitals in the United Kingdom over a 27-month period, during which there were 24,059 episodes of AKI.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Such a study using e-alerts for AKI defined by serum creatinine level, and not machine learning surveillance as in the present study, found a reported increase in AKI, a reduced length of stay, and improvements in the quality of care but no change in the 30-day AKI mortality rate. 17 Perhaps machine learningemediated surveillance, with earlier recognition of AKI, will offer additional improvements in the care of the patient with AKI. The exciting prospect that machine learningemediated surveillance may confer salutary outcomes in AKI and reduce attendant morbidity and mortality should be examined in further studies.…”
mentioning
confidence: 99%